2021
DOI: 10.1051/e3sconf/202127103024
|View full text |Cite
|
Sign up to set email alerts
|

Exercise in Patients with Non-cardiac Myocardial Injury under Optical Microscope

Abstract: In recent years, the incidence of cardiovascular disease has been increasing year by year, has gradually developed into a global health problem, in the world wide concern. Non - cardiac injury is one of the most common cardiovascular diseases. The rehabilitation of patients with non-cardiac myocardial injury is related to their life and quality of life. Rehabilitation exercise is helpful to improve the therapeutic effect of patients. The purpose of this paper is to explore the specific effects of rehabilitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Along with the development of society, the incidence of cardiovascular diseases worldwide is increasing year by year, and this trend is becoming increasingly fierce among young and middle-aged people [ 1 ]. It is reported that there are 330 million people suffering from cardiovascular diseases in China, among which 11 million are coronary heart disease (CHD) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Along with the development of society, the incidence of cardiovascular diseases worldwide is increasing year by year, and this trend is becoming increasingly fierce among young and middle-aged people [ 1 ]. It is reported that there are 330 million people suffering from cardiovascular diseases in China, among which 11 million are coronary heart disease (CHD) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%